2016
DOI: 10.1080/21645515.2016.1145847
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to respiratory syncytial virus infection in children <18 months old

Abstract: The development of a safe and effective respiratory syncytial virus (RSV) vaccine might be facilitated by knowledge of the natural immune response to this virus. The aims of this study were to evaluate the neutralizing antibody response of a cohort of healthy children <18 months old to RSV infection. During the RSV season, 89 healthy children <18 months old were enrolled and followed up weekly for 12 weeks. At each visit, a nasopharyngeal swab was obtained for RSV detection by real-time polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…1 Overall, HRSV was detected in 17% of investigated patients. This rate agrees with those of previous reports, including in Senegal (11%), 17 Italy (11%), 18 and Canada (25%). 5 HRSV infection was predominant in younger children (<6 months), and bronchiolitis was the most frequent diagnosis, which is consistent with our previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…1 Overall, HRSV was detected in 17% of investigated patients. This rate agrees with those of previous reports, including in Senegal (11%), 17 Italy (11%), 18 and Canada (25%). 5 HRSV infection was predominant in younger children (<6 months), and bronchiolitis was the most frequent diagnosis, which is consistent with our previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…Even in the absence of serologic confirmation, a positive RT-PCR result with these viruses would be sufficient for disease association. For example, RT-PCR detected RSV in 38 children younger than 6 months who did not develop a seroresponse, which is consistent with studies that have shown that infants do not develop effective immune responses to RSV, especially following initial infection (25). Because subclinical infections with RSV are rare, RSV was likely causally related to the illness in these cases.…”
Section: Discussionsupporting
confidence: 71%
“…This could suggest an important involvement of the immune response to the virus and a role for different immune mechanisms in response to the virus in preterm infants. Indeed, there are many evidences about lack of immunity in preterm children, regarding count and activity of all subsets of T cells [36] and deficient antibody production in younger infants infected with RSV [37]. Since various components of the innate and adaptive immune response are crucial for controlling RSV infection and disease [38], more studies are needed to focus preterm specific immune response.…”
Section: Discussionmentioning
confidence: 99%